KETIKA BEA MASUK ANTIDUMPING TIDAK DAPAT MENGOREKSI MONOPOLI, PERLUKAH DIKENAKAN? PELAJARAN DARI PENGENAAN BEA MASUK ANTIDUMPING TERHADAP LISIN RRT - Yustinus B. Solakira (UNES Law Review, 2023)
Anti-dumping measures are truly a limited exemption from multilateral agreements on tariff elimination under WTO. This exemption is provided under WTO laws in order to remedy domestic industry’s injury caused by dumping, which is viewed not only as an unfair trade practice but also as unfair competition behaviour. Ironically, the imposition of antidumping measure on lysine importation from People’s Republic of China even brings about an anti-competitive impact on domestic industry. An antidumping measure which is aimed at condemning predatory price fixing even creates a monopoly within domestic industry for the like product.The imposition of the antidumping measure eventually eliminate competitors from the relevant market and leave a domestic producer in the market as a single supplier. So, the questions here are: how the antidumping measure has been considered so that such a measure aming at overcoming an unfair trade practice and an unfair competition can bring about an anti-competitive impacts on domestic industry? Can an antidumping measure make a correction to unfair competition in domestic industry? This paper is going to discuss and answer those questions.